2009
DOI: 10.1075/term.15.1.02fer
|View full text |Cite
|
Sign up to set email alerts
|

Terminology and terminography for architecture and building construction

Abstract: Teaching terminology is a strategic response to the European Educational Convergence guidelines, taken by the Polytechnic University of Madrid. It is vested in a new course "English Terminology for Architecture and Building Construction" offered in the "Master of Techniques and Systems of Construction". The course is interdisciplinary, integrating material from the various sciences involved in architectural practice and exploring it through the discipline of applied linguistics, as recommended by Cabré (2003).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For language teachers who are uncomfortable teaching technical terms, it has been suggested that they can engage learners in identifying what words are central to a specific topic or area (Alcina 2011;Fernádez et al 2009). Instead of trying to become vocational authorities, language teachers can concentrate on their role as language experts and help learners become aware and develop their repertoire of vocabulary strategies (Chung and Nation 2003) and support their students' language awareness and ability to recognize technical terms (Nation 2001).…”
Section: Principles For Teaching Vocabularymentioning
confidence: 99%
See 1 more Smart Citation
“…For language teachers who are uncomfortable teaching technical terms, it has been suggested that they can engage learners in identifying what words are central to a specific topic or area (Alcina 2011;Fernádez et al 2009). Instead of trying to become vocational authorities, language teachers can concentrate on their role as language experts and help learners become aware and develop their repertoire of vocabulary strategies (Chung and Nation 2003) and support their students' language awareness and ability to recognize technical terms (Nation 2001).…”
Section: Principles For Teaching Vocabularymentioning
confidence: 99%
“…This raises the question of whether the teachers are in a position to select vocabulary that represents core aspects of their students' vocational learning. To ameliorate what can be seen as a problematic situation, we build on Alcina (2011), Fernádez et al (2009, Chung and Nation (2003), and Nation (2001), whom all argue that there is no need for English teachers to be vocational experts to succeed in teaching vocational terminology. Instead, English teachers in vocational education can retain their role as language experts and focus on facilitating vocational language encounters.…”
Section: Word Choicementioning
confidence: 99%